Online file sharing and copyright management in the digital age - Badilles, Cristher Emely; Demegillo, Hechille Rose.; Eguia, Nanelyn; Sedigo, Cristine Marie; Simeon, Adamae Joy.; Torejo, Marichelle (2009.)
The study examines the possible effects of Digital Rights Management on online file sharing of information goods. It also looks at the key factors affecting Digital Rights Management (DRM) and online file sharing, provides copyright initiatives for both Internet usrs and creative owners, and proposes policy enhancements to the existing legislations, enforcement agencies, and DRM practices. The respondents of the study include 75 BS in Management students, 34 of which are third year students and 41 fourth year students of the University of the Philippines in the Visayas in Iloilo City. Descriptive analysis was made on the two major variables of the study. As a whole, the effects of Digital Rights Management practices to online file sharing remain unclear since today's digital environment had grown very complex than ever. More and more ways were developed to increase possibility of free access to digital contents. Most of the respondents believe that online files are very easy to access. Moreover, only a few of them are aware of the current policies that prohibit acquisition of copyrighted materials over the Internet. Even though some are aware, illegal access is still being practiced and they continue to be involve in online file sharings. The Optical Media Board of the Philippines, the agency responsible for implementing legislations to combat Internet piracy, admitted that it is indeed difficult to locate and hinder billions of virtually dispersed Internet users from obtaining digital files. A television campaign was made to inform the public but it only focused to an anti-piracy campaign against pirated digital video disks (DVD's) and compact disks (CD's) that weakened the movie and music industries. Other forms of digital piracy such as accessing online documents and softwares were not addressed specifically. As a result, the number of Internet users engaging in illegal online file access continue to increase and they do not have to worry about being penalized. Given the aforementioned problems, the study recommend the local government to reevaluate their current policies, innovate means of addressing the problems, and increase the scope of their campaigns, i.e. conducting regional programs against digital piracy to increase public awareness and develop individual accountability. On the other hand, owners of original digital files should use methods such as enabling user name and password options, adding digital watermarks or pieces of information added to digital data to detect unauthorized copies, and including copyright notice and registrations to their originally owned digital materials.
Research Proposal (Mgt 199 - Management Research) -- [Iloilo City : Unversity of the Philippines Visayas-College of Management], October 14, 2009.